Komparasi Muatan Gaya Bahasa dalam Iklan Minuman Kemasan Siap Minum: Kajian Stilistika - Riqko Nur Ardi Windayanto (Faculty of Languages and Arts, Universitas Negeri Padang, 2021)
Advertising is the most effective media for promoting the products. Through advertising, the product marketing uses the language that is very likely to contain language styles with specific functions. This study aims to reveal the content and function of language style and its comparison in advertisements of three groups of drinks, namely tea, fruit juice, and milk, with a stylistic approach. The data is obtained by digital ethnography method and note-taking technique that is used to classify visual data and verbal data. Data analysis is carried out by interpreting verbal data and visual data based on a stylistic approach that is explored by using multimodal analysis. The results show that the tea advertisements contain idioms, rhetoric, figures of speech, language style based on structure and tone, and diction. Fruit juice advertisements contain denotative, rhetorical, figurative, and stylistic meanings based on tone. Milk advertisements contain rhetoric, figures of speech, figurative language based on structure and tone, as well as diction. Although they have their own quantity and quality, the language styles in the three products have the same functions, namely informing excellence; suggesting consumers; and branding the product.